Clinicopathological features and prognosis of gastric cardia adenocarcinoma: A multi‐institutional U.S. study. Issue 3 (10th October 2014) - Amini, Neda; Spolverato, Gaya; Kim, Yuhree; Squires, Malcolm H.; Poultsides, George A.; Fields, Ryan; Schmidt, Carl; Weber, Sharon M.; Votanopoulos, Konstantinos; Maithel, Shishir K.; Pawlik, Timothy M.
<x xml:space="preserve">Abstract</x> Background and Objectives Potential differences in presentation and outcome of patients with gastric cardia adenocarcinoma (GCA) and non‐cardia adenocarcinoma may exist. The aim of the present study was to compare the clinicopathological characteristics and the prognosis of GCA versus non‐cardia adenocarcinoma. Method Patients with gastric adenocarcinoma who underwent gastric resection between 2000–2012 were identified. Clinicopathological characteristics and outcomes were analyzed based on tumor site using a 1:2 matched‐control, as well as a multivariable Cox model. Results Among 743 patients, 80 (10.7%) patients were diagnosed with GCA. Patients with GCA were more likely to have intestinal tumor type (GCA: 80.4% versus non‐cardia: 64.2%, P = 0.04) or advanced AJCC T stage tumors (GCA 71.8% versus non‐cardia 59.2%, P = 0.03). GCA patients more likely underwent a total gastrectomy (GCA: 85.7% vs. non‐cardia: 39.8%) and had a longer length‐of‐stay (GCA: 10 days vs. non‐cardia: 8 days) (both P < 0.05). Outcomes in early stage I patients were worse among GCA (disease‐free survival, 44.2%; overall survival, 42.3%) versus non‐GCA (disease‐free survival, 60.8%; overall survival, 63.0%) patients(both P < 0.05). Conclusion In general, disease‐free survival and overall survival were similar between patients with GCA versus non‐cardia adenocarcinoma. However, long‐term outcome was worse among patients with GCA and early stage disease. J. Surg. Oncol. 2015 111:285–292. © 2014 Wiley Periodicals, Inc.